Assessment of the carp seeds value chain in Southern Bangladesh - WorldFish (WorldFish, 2012)
The Aquaculture for Income and Nutrition (AIN) project implemented by World Fish and funded by USAID, aims at increasing aquaculture production in 20 districts of Southern Bangladesh (Greater Khulna, Greater Barisal, Greater Jessore and Greater Faridpur) to reduce poverty and enhance nutritional status. As part of its initial scoping activities World Fish commissioned this value chain assessment on the market chains of carp fish seed (spawn, fry and fingerlings) in the southern region of Bangladesh. The purpose of this study is to obtain a clearer understanding of the volumes of fish produced and consumed in Southern Bangladesh and their origin (by system and location), their destination (by type of market, type of consumer and location), and to gain a clearer understanding of potential market based solutions to farmer’s problems, which the project could implement.